2017
DOI: 10.1111/acel.12653
|View full text |Cite
|
Sign up to set email alerts
|

The valosin‐containing protein is a novel repressor of cardiomyocyte hypertrophy induced by pressure overload

Abstract: SummaryHypertension‐induced left ventricular hypertrophy (LVH) is an independent risk factor for heart failure. Regression of LVH has emerged as a major goal in the treatment of hypertensive patients. Here, we tested our hypothesis that the valosin‐containing protein (VCP), an ATPase associate protein, is a novel repressor of cardiomyocyte hypertrophy under the pressure overload stress. Left ventricular hypertrophy (LVH) was determined by echocardiography in 4‐month male spontaneously hypertensive rats (SHRs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(69 citation statements)
references
References 44 publications
3
66
0
Order By: Relevance
“…Whereas banding results in a sudden increase in RV afterload, RV systolic pressures take approximately three weeks to increase in the monocrotaline and SuHx rat models of PAH. In the rat, a sudden increase in aortic pressure in the transverse aortic constriction model of left-ventricular hypertrophy is associated with more pronounced chamber remodeling than the more gradual spontaneously hypertensive rat [20]. Although most RV hemodynamic measurements were not different between rats 5 and 6 weeks after SuHx as used here, 4 weeks after monocrotaline [5], and 3 weeks after PA banding [8], one exception was mean RV end-diastolic volume.…”
Section: Discussionmentioning
confidence: 68%
“…Whereas banding results in a sudden increase in RV afterload, RV systolic pressures take approximately three weeks to increase in the monocrotaline and SuHx rat models of PAH. In the rat, a sudden increase in aortic pressure in the transverse aortic constriction model of left-ventricular hypertrophy is associated with more pronounced chamber remodeling than the more gradual spontaneously hypertensive rat [20]. Although most RV hemodynamic measurements were not different between rats 5 and 6 weeks after SuHx as used here, 4 weeks after monocrotaline [5], and 3 weeks after PA banding [8], one exception was mean RV end-diastolic volume.…”
Section: Discussionmentioning
confidence: 68%
“…Primary cultures of neonatal rat cardiac myocytes were prepared as described previously . Briefly, 1‐ to 2‐day‐old Sprague Dawley rats were killed by swift decapitation and their hearts were immediately removed under aseptic conditions and placed in ice‐cold sterile PBS (calcium‐ and magnesium‐free).…”
Section: Methodsmentioning
confidence: 99%
“…Mice were anesthetized by inhalation of 2% isoflurane. Transthoracic echocardiographic analysis was performed using an animal‐specific instrument (VisualSonics Vevo770, VisualSonics Inc., Canada) as previously described . Mice were anesthetized and M‐mode images of the left ventricle (LV) were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, VCP has been found to play an essential role in mitochondrial function, including mitochondrial respiration, ATP production and mPTP opening. Overexpression of the VCP protects cardiomyocyte against stimulated death and reduces the I/R induced infarct size in the heart [ 13 , 90 , 91 , 92 ]. Notably, the most recent study found that VCP protects the heart from the stress by preventing excessive Ca 2+ overload through inhibiting Ca 2+ uptake [ 13 ].…”
Section: Other Regulators In Mitochondrial Ca 2+ mentioning
confidence: 99%